2009
DOI: 10.1097/aog.0b013e3181ac4e18
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus Bacteremia and Chorioamnionitis After Recurrent Marsupialization of a Bartholin Abscess

Abstract: Our case and the literature suggest that it may be prudent to consider MRSA when contemplating the possibility of chorioamnionitis in the presence of intact fetal membranes, especially in gravidas with recurrent admissions or minor surgical procedures or who are hospital staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…50 Case reports of chorioamnionitis include cases associated with employment in healthcare, marsupialization of Bartholin's gland during pregnancy, and PPROM. 25,51 There is relatively little data correlating maternal and neonatal infection. In one relatively small series, Pinter reported that 20% of neonatal infections with S. aureus were the result of vertical transmission 52 ; Andrews found MRSA genital colonization in 3.5% of mothers in a series of more than 5000 deliveries, but no early-onset neonatal disease.…”
Section: Chorioamnionitismentioning
confidence: 98%
“…50 Case reports of chorioamnionitis include cases associated with employment in healthcare, marsupialization of Bartholin's gland during pregnancy, and PPROM. 25,51 There is relatively little data correlating maternal and neonatal infection. In one relatively small series, Pinter reported that 20% of neonatal infections with S. aureus were the result of vertical transmission 52 ; Andrews found MRSA genital colonization in 3.5% of mothers in a series of more than 5000 deliveries, but no early-onset neonatal disease.…”
Section: Chorioamnionitismentioning
confidence: 98%
“…Examples of this growing list of MRSA infections include meningitis,[56] epidural abscess,[57] neonatal liver abscess,[58] mastitis and toxic shock syndrome,[59] and even chorioamnionitis. [60]…”
Section: Types Of Mrsa Infectionsmentioning
confidence: 99%
“…6 Antepartum complications of pregnancy associated with MRSA infections are uncommon yet include rare cases of chorioamnionitis. [7][8][9] Recently reported severe adverse postpartum complications attributed to MRSA include a patient with a wound abscess, septicemia, septic thrombophlebitis, and a septic pulmonary embolism. 7 The nonobstetric literature confirms that approximately 85% of MRSA infections involve the skin and subcutaneous tissue, with the most common presentations being an abscess or folliculitis.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Recently reported severe adverse postpartum complications attributed to MRSA include a patient with a wound abscess, septicemia, septic thrombophlebitis, and a septic pulmonary embolism. 7 The nonobstetric literature confirms that approximately 85% of MRSA infections involve the skin and subcutaneous tissue, with the most common presentations being an abscess or folliculitis. 10 Abscesses are generally considered to respond favorably to drainage.…”
Section: Discussionmentioning
confidence: 99%